Dermatosis Ictiosiforme y manchas hipocromicas como manifestaciones clinicas de Linfoma Cutaneo de Celulas T Relacionadas con HTLV - Calero, Gonzalo (Revista Universidad de Guayaquil, 1998)
We describe a black patient who is seropositive for HTLV, who presented with generalized ichthyosiform dermatosis, with hypochromic macules especially on the lower extremities, as well as palmoplantar keratodermia. Histopathology suggestive of T-cell cutaneous lymphoma leads us to believe that this is the first reported case of stage IB T-cell cutaneous lymphoma related to HTLV-I in Ecuador according to clinical, histological, and serological data.